Partnership Models to Strengthen the Promotion of Sustainable Tourism at Gunung Padang Site, Tourism Destination, West Java, Indonesia - Sorongan, Fangky Antoneus; Hermawan, Hardy R; Permata, Jan Prince; Fahlevi, Raka; Prayitno, Deden; Legowo, Mercurius Broto; Mahad, Haniza; Yusof, Rahmawati Mohd; Trang, Trần Trương Thanh (Universitas Veteran Bangun Nusantara, 2025)
The Gunung Padang site in West Java is a cultural and historical tourism destination with great potential to attract domestic and international tourists. However, the promotion of this destination still faces several challenges, including limited infrastructure, suboptimal use of digital technology-based promotions, and a lack of strong synergy among stakeholders. This International Community Service Activity aims to develop an effective partnership model through the Penta Helix model, thereby strengthening the promotion of the Gunung Padang Site in West Java, Indonesia. Using a descriptive qualitative approach, this study collected data through in-depth interviews, field observations, and document analysis, involving local government officials, site managers, local communities, academics, and tourism industry players. The results of this community service activity show that the Pentahelix-based partnership model (government, academics, business sector, community, and media) can increase synergy in the promotional strategy for the Gunung Padang site destination in West Java. Through this collaborative activity, we can optimize digital promotion and develop integrated tourism packages. At the same time, we can increase local community involvement to support destination sustainability. Implementing this inclusive partnership model effectively strengthens the competitiveness of the Gunung Padang Site as a leading tourism destination in West Java.